Evaluation of Management Earnings Forecast Error and Information Content of Accruals: Listed Companies in Tehran Stock Exchange - Moradzadehfard, Mehdi (Journal of Education and Vocational Research, 2013)
Aim of this study is studying relation of management earnings forecast error and information content of accruals. Thus, the sample consists of 71 companies were selected for the period 2003-2011. In this study discretionary accruals is used as independent variables. The results suggest that there is a significant negative relationship between earnings management forecast error and the total discretionary accruals. These results indicate that other assumptions that management forecasts for financing through equity or debt generates a significant positive relationship between positive accruals and management earnings forecast error. In addition, through equity or debt financing outlook, there is no significant relationship between earnings forecast error and negative accruals.